Studi Pemulihan Fungsi Das Berdasarkan Tingkat Kekritisan Lahan Dan Potensi Kelongsoran Di Sub Das Jeneberang Hulu - Nurdin, Fajar Arif; Bisri, Mohammad; Rispiningtati, Rispiningtati; Priyantoro, Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Watershead management is a serious problem because of increasing number of critical land as the impact of land management that is not accordance with its ability and not accompanied by efforts of conserve soil and water, and also changes in patterns of land use vegetated. Sub watershed of upstream jeneberang with area 38.552 ha located on the upstream of the Dam Bilibili have problems of watershed damage that is erosion and landslides are an indicator of failure in managing the natural resources that have a public benefit. Based on the analysis result of AVSWAT 2000 showed amount of land area that has an erosion rate in class V (>480 tons/ha/year) reached 3.390,21 ha (8.79% of the total sub watershed upstream jeneberang). Then, from the result of classification susceptibility/degradation level in watershed upstream Jeneberang, obtained critical area of high category 5.820,98 ha (15,11%). The amount of critical land dominated by the land use, open land and garden. Whereas for landslide susceptibility levels, obtained the land area is prone to landslides covering an area of 9.819,36 ha (25,47%) in area with slope class 26-45% and 46-65%. Efforts completion of the real problems in the field is done within depth consideration of the characteristics of the watershed upstream. Recommendations is the form of proposed activities is expected to provide a framework and a common perception that fasilitate the stakeholders to cooperate in an effort of utilization and conservation of natural resources effectively and efficiently to improve the ecosystem stability and prosperity of the community and also preservation of the integrity of watershed function.Keywords: Watershed management, AVSWAT 2000, Erosion, Landslide, Conservation.